Understanding Risk Factors for Opioid Overdose in Clinical Populations to Inform Treatment and Policy. Issue 6 (November 2016) - Park, Tae Woo; Lin, Lewei Allison; Hosanagar, Avinash; Kogowski, Amanda; Paige, Katie; Bohnert, Amy S.B.
Abstract : Overdoses involving opioid analgesics represent a significant public health problem in the United States. We reviewed the literature on risk factors for overdose, with a focus on studies that examine clinical populations of patients receiving opioids for pain and potential risk factors for overdose in these populations. A structured review resulted in 15 articles published between 2007 and 2015 that examined risk factors for fatal and nonfatal overdose in patients receiving opioid analgesics. Opioid dosage was the factor most consistently analyzed and also associated with increased risk of overdose. Other risk factors include concurrent use of sedative-hypnotics, use of extended-release/long-acting opioids, and the presence of substance use and other mental health disorder comorbidities. Future research is needed to better characterize populations taking opioids for pain to help clarify discrepancies between existing studies and identify previously unexplored risk factors for overdose. Given that policy and clinical practice have shifted as a result of prior studies reviewed here, further efforts in understanding patient groups and opioid-related prescribing practices associated with overdose risk have great potential to impact policy and practice in the treatment of pain while improving the safety around opioid prescribing.